2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944307
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of motion artifact induced by exercise for PPG-based heart rate sensing

Abstract: Heart rate (HR) sensing during exercise is essential for medical, healthcare and sport physiological purposes. Photo-Plethysmo-Graphy (PPG) is a simple and non-invasive technique for HR sensing, but it is highly sensitive to motion artifact. This paper proposes a cancellation technique of motion artifact in PPG-based HR sensing for a man during exercise. The canceller is equipped with two sensors; one is a normal PPG sensor where an LED/Photo-Detector (PD) contacts the skin to detect Blood Volume Pulse (BVP) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…The effect of the two design parameters are examined in [13]. In addition, we confirmed that the proposed HR sensor works well for several exercises and motions such as standing-still, walking, fast-walking, running, jumping [12], [13] and deep breathing [14]. Furthermore, it should be noted that, defining the transversal filter output as y(n), the weight control algorithm tries to make the error e(n) between d(n) and y(n) be zero and BVP is obtained as "a residual error."…”
Section: Suitable Positions Of Vital Sensorssupporting
confidence: 57%
See 1 more Smart Citation
“…The effect of the two design parameters are examined in [13]. In addition, we confirmed that the proposed HR sensor works well for several exercises and motions such as standing-still, walking, fast-walking, running, jumping [12], [13] and deep breathing [14]. Furthermore, it should be noted that, defining the transversal filter output as y(n), the weight control algorithm tries to make the error e(n) between d(n) and y(n) be zero and BVP is obtained as "a residual error."…”
Section: Suitable Positions Of Vital Sensorssupporting
confidence: 57%
“…Especially when a sensor wearer exercises vigorously, the frequency component of the MA overlaps with that of the HR, so the MA cannot be canceled by a linear filter such as band pass filter (BPF). Figure 3 shows the principle of the MA canceling PPGbased HR sensor [12]. The proposed HR sensor is equipped with two LED/PDs.…”
Section: Suitable Positions Of Vital Sensorsmentioning
confidence: 99%
“…The few previous studies that evaluated wrist-based HR accuracy using PPG revealed conflicting results (Gorny, Liew, Tan, & Muller-Riemenschneider, 2017). Movement artefacts are thought to be a problem in the wrist-worn pulse rate measurements using PPG (Tamura, Maeda, Sekine, & Yoshida, 2014;Zhang, Pi, & Liu, 2015), especially during activities with increased intensity or particular arm and wrist movements (Gorny et al, 2017;Shimazaki, Hara, Okuhata, Nakamura, & Kawabata, 2014;Spierer, Rosen, Litman, & Fujii, 2015;Stahl, An, Dinkel, Noble, & Lee, 2016). Moreover, factors such as skin colour, skin temperature or body mass index (BMI) were shown potentially to affect measurement accuracy (Khan et al, 2015;Spierer et al, 2015;Valenti & Westerterp, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3 (c) shows the relationship between the measured VO2 and the estimated VO2 by (7) with L=3 instead of (4). We can see in the figure a good agreement between the measured and estimated VO2s, but there is still a big problem in the EE sensing.…”
Section: B Ee Sensingmentioning
confidence: 99%
“…We have developed a vital signs monitoring system for two years in 2012 and 2013 [3][4][5][6][7]. It can collect and monitor vital signs such as HR, EE and BT from all (twenty two) players during a football game in real-time, periodically and reliably.…”
Section: Introductionmentioning
confidence: 99%